2003
DOI: 10.1093/molehr/gag083
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of angiopoietins 1 and 2 and their receptor Tie-2 in human endometrium

Abstract: Angiogenesis, the growth of new capillaries from pre-existing blood vessels, is a physiological process involved in both normal menstrual cycling and implantation of the embryo. So far, very little is known about the expression of angiopoietins, growth factors involved in angiogenesis, in human endometrium. Both angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2) are ligands for the endothelial cell-specific receptor tyrosine kinase Tie-2. In this study we determined the mRNA expression of Ang-1, Ang-2 and Tie-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
5
26
0
6
Order By: Relevance
“…The expression of Tie-2 protein was dominated by glandular epithelial cytoplasm, and a small amount of vascular endothelial cells and cytoplasm of interstitial cells were expressed in varying degrees, but weak. This is consistent with the findings of Hirchenhain et al [9] The experiment also showed that Ang-2 and Tie-2 protein expressions in EMs eutopic endometrium group were higher than that in the normal group. This is consistent with the findings of Hur et al, [7] suggesting that endometrium may carry out stronger angiogenic activity.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of Tie-2 protein was dominated by glandular epithelial cytoplasm, and a small amount of vascular endothelial cells and cytoplasm of interstitial cells were expressed in varying degrees, but weak. This is consistent with the findings of Hirchenhain et al [9] The experiment also showed that Ang-2 and Tie-2 protein expressions in EMs eutopic endometrium group were higher than that in the normal group. This is consistent with the findings of Hur et al, [7] suggesting that endometrium may carry out stronger angiogenic activity.…”
Section: Discussionsupporting
confidence: 92%
“…Ang-1 has been immunolocalized to all cell types within endometrium (Blumenthal et al, 2002;Saito et al, 2007) and has been reported to either increase (Hirchenhain et al, 2003;Saito et al, 2007) or not alter (Blumenthal et al, 2002;Hur et al, 2006;Lee et al, 2008) as the menstrual cycle progresses. Ang-2 is also widely expressed in endometrium with levels reported to be decreased (Hirchenhain et al, 2003;Saito et al, 2007), unaltered (Blumenthal et al, 2002;Hewett et al, 2002;Hur et al, 2006) or increased (Lee et al, 2008) as the menstrual cycle progresses. Tie-2 expression is also widespread in the endometrium and has been reported to not alter with the menstrual cycle (Blumenthal et al, 2002;Hewett et al, 2002;Hirchenhain et al, 2003;Hur et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ang-2 is also widely expressed in endometrium with levels reported to be decreased (Hirchenhain et al, 2003;Saito et al, 2007), unaltered (Blumenthal et al, 2002;Hewett et al, 2002;Hur et al, 2006) or increased (Lee et al, 2008) as the menstrual cycle progresses. Tie-2 expression is also widespread in the endometrium and has been reported to not alter with the menstrual cycle (Blumenthal et al, 2002;Hewett et al, 2002;Hirchenhain et al, 2003;Hur et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Staining has been reported variously in the epithelium, stroma and uterine natural killer cells (reviewed in Rogers & Abberton (2003)). In one study, ANG1 immunostaining was observed in stroma, luminal and glandular epithelium, and endothelial cells, whereas ANG2 was detected in the stroma and glandular epithelium (Hirchenhain et al 2003). TIE2 was observed in glandular epithelium, as well as in endometrial endothelium.…”
Section: Endometrial Vascular Remodellingmentioning
confidence: 94%